2019
DOI: 10.1002/ijgo.13023
|View full text |Cite
|
Sign up to set email alerts
|

Trends and predictors of gestational diabetes mellitus in Chile

Abstract: ObjectiveTo examine the temporal trends in gestational diabetes mellitus (GDM) prevalence in Chile, and to determine the main predictors of GDM.MethodsA secondary analysis was conducted of all birth records at Hospital Dr. Sótero del Río, Chile, from January 1, 2002, to December 31, 2015. We excluded those women with pre‐existing type 2 diabetes, those with missing data, and those with unlikely data. GDM was defined as fasting glucose levels >5.55 mmol/L [>100 mg/dL] or >7.77 mmol/L [>140 mg/dL] 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 32 publications
7
25
2
5
Order By: Relevance
“…According to these arguments, coordinated efforts are required to provide better perinatal management and postpartum preventive strategies to modify these trends and to evade the ''vicious cycle'' in which diabetes causes more diabetes 2,46 . In this sense, countries with high rates of obesity are related to the highest rates of diabetes and our country is not an exception, in which the prevalence of GDM has increased from 4.4% in 2012 to 13% in 2015 47 …”
Section: Discussionmentioning
confidence: 99%
“…According to these arguments, coordinated efforts are required to provide better perinatal management and postpartum preventive strategies to modify these trends and to evade the ''vicious cycle'' in which diabetes causes more diabetes 2,46 . In this sense, countries with high rates of obesity are related to the highest rates of diabetes and our country is not an exception, in which the prevalence of GDM has increased from 4.4% in 2012 to 13% in 2015 47 …”
Section: Discussionmentioning
confidence: 99%
“…PE also affects the occurrence of GDM; a retrospective cohort study in Korea showed that a history of PE in first pregnancy is a risk factor for the development of GDM in subsequent pregnancies ( 50 ). However, a retrospective study in Chile suggested that the history of PE in previous pregnancies is negatively associated with the occurrence of GDM in the next pregnancy ( 13 ). Whether PE associated with the occurrence of GDM should be further confirmed in large sample studies.…”
Section: Correlation Between Gdm and Pementioning
confidence: 99%
“…GDM is currently the most common medical complication of pregnancy and the prevalence of undiagnosed hyperglycemia and even overt diabetes in young women is increasing ( McIntyre et al, 2019 ). In Chile, 1 in 8 pregnant women of middle socioeconomic status has GDM ( Garmendia et al, 2020 ), and 5–10% of women with GDM develop type 2 diabetes after delivery, maintaining a linear growth ( Auvinen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…GDM in the health care system has tripled over a 14-years period, which could be explained by changes in the trend of risk factors during this period ( Garmendia et al, 2020 ), such as the increased prevalence of obesity, along with later fertility which has been associated with higher risk gestation. All this results in an increased burden of care and demand for specialized services ( Ministerio de Salud, 2014 ).…”
Section: Introductionmentioning
confidence: 99%